(untitled) (Al-Qamar, 2023)
The constant practices of generations give rise to a unique culture for each region, nation, and tribe. These cultural differences can be attributed to varying factors such as food, weather, and habits. This article examines the Arab culture prior to Islam and its perspective on divorce. Important topics discussed in the article include the definition and methods of divorce, women’s right to divorce, divorce statistics, reasons for divorce, Rajjo and Eddat, regulations regarding previous pregnancy, and rules regarding family expenses and residence. By comparing Arab traditions under Islamic law, the article aims to demonstrate that not all traditions were rejected, but rather unacceptable practices were eliminated, acceptable practices were retained, and those that required improvement were reformed to become part of the religion. This methodological approach is critical in addressing cultural issues.